VISUAL LEARNING AND COGNITIVE ENGAGEMENT: ANIMATION AS A TOOL FOR KNOWLEDGE TRANSFER IN DIGITAL EDUCATION - Saniya Assembek (Modern American Journals, 2025)
In the context of the rapid development of digital technologies, animation is becoming a key tool for visual learning in the modern education system. The article reveals the theoretical foundations of the use of animation in the educational process, based on the cognitive theories of J. Sweller and R. Mayer, and emphasizes its role in reducing cognitive load and increasing student engagement. The psychological aspects of the perception of moving visual images, as well as the principles of inclusive and accessible design are considered. The presented empirical studies demonstrate the positive impact of animation on knowledge acquisition, especially in the context of distance and hybrid learning. In conclusion, practical recommendations for the effective use of animation technologies in the context of digital education are formulated.
Keywords: Animation, visual learning, cognitive load, multimedia learning, inclusion, digital education, interactive content, cognitive engagement, accessibility-first.